Improving Learning Outcomes of Electrical Lighting Installation with Project-Based Learning at SMKN 3 Tondano - Lembong, Jemmy; Tatali, Yosua (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to determine whether there are differences in learning outcomes of psychomotor abilities in designing and installing Electrical Lighting Installations implementing a project-based learning methodology with students using traditional learning models in class XI TITL SMK Negeri 3 Tondano. This study used an experimental method, with a sample of 15 students of XI TITL 1 as the experimental class and 15 students of XI TITL 2 as the control class. Data analysis was carried out by t-test and requirements test, namely normality test using Lilieforce test and the Levene test. The results showed a difference between the learning outcomes of designing and installing electrical lighting installations for groups of students implementing a project-based learning methodology with students using traditional learning models. The average psychomotor ability learning outcomes of students who use project-based learning models are higher than those of conventional learning models. Based on this statement, it can be concluded that there is an effect of project-based learning models to improve students' psychomotor learning outcomes in the material of designing and installing Electrical Lighting Installations in class XI students of SMK Negeri 3 Tondano.